Басни - Крылов Иван Андреевич (Школьная библиотека для нерусских школ, 1978)
Экземпляры: (20201005) / Инвентарный номер: 25456 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: К 85 / ГРНТИ: 17.82.70 / ББК: 84(2Рос=Рус)1